2008
DOI: 10.1093/nar/gkn120
|View full text |Cite
|
Sign up to set email alerts
|

Structural polymorphism within a regulatory element of the human KRAS promoter: formation of G4-DNA recognized by nuclear proteins

Abstract: The human KRAS proto-oncogene contains a critical nuclease hypersensitive element (NHE) upstream of the major transcription initiation site. In this article, we demonstrate by primer-extension experiments, PAGE, chemical footprinting, CD, UV and FRET experiments that the G-rich strand of NHE (32R) folds into intra-molecular G-quadruplex structures. Fluorescence data show that 32R in 100 mM KCl melts with a biphasic profile, showing the formation of two distinct G-quadruplexes with Tm of ∼55°C (Q1) and ∼72°C (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
170
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 67 publications
6
170
0
1
Order By: Relevance
“…It occurs by heteromodification of histones, which promotes the decondensation of high order chromatin, and by binding to enhancer/promoter regulatory cis-elements (44). Previous studies have reported that PARP-1 recognizes unusual DNA conformations such as hairpins/cruciforms (47)(48)(49) and the G-quadruplex formed by a cis-element in the human KRAS promoter (8). Interestingly, Ladame and co-workers (50) have shown that PARP-1 undergoes automodification after binding to the c-kit quadruplex.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs by heteromodification of histones, which promotes the decondensation of high order chromatin, and by binding to enhancer/promoter regulatory cis-elements (44). Previous studies have reported that PARP-1 recognizes unusual DNA conformations such as hairpins/cruciforms (47)(48)(49) and the G-quadruplex formed by a cis-element in the human KRAS promoter (8). Interestingly, Ladame and co-workers (50) have shown that PARP-1 undergoes automodification after binding to the c-kit quadruplex.…”
Section: Discussionmentioning
confidence: 99%
“…As G4-decoy 2998 binds to proteins recognizing G4-proximal (PARP-1, Ku70, hnRNP A1, MAZ)9, it inhibits KRAS transcription by a decoy mechanism. As a consequence, the proliferation and clonogenic potential of Panc-1 cells are reduced by the G4-decoy oligonucleotide12.…”
Section: Resultsmentioning
confidence: 99%
“…Given the strong impact of KRAS G12D on the metabolism of PDAC cells, this oncogene is an attractive target for new anticancer drugs. For a rationale design of anticancer drugs we focused on the KRAS promoter, as it contains three G4 motifs, of which the one most close to TSS, G4-proximal, has been extensively studied8910. G4-proximal is located between −144 and −117 upstream of TSS, overlaps a nuclease hypersensitive element (NHE) and is recognized by several nuclear proteins including MAZ, PARP-1, Ku70/Ku80 and hnRNP A110.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on DNA quadruplex sequences and used the human telomeric G-quadruplex (H-telo) [6] and the sequences of the promoter quadruplexes of a selection of genes, namely c-kit (which contains the two G-quadruplex sequences c-kit1 [39] and c-kit2 [40] ), c-myc , [5b, 41] bcl2 [42] and k-ras . [43] These different sequences differ in composition, in the number of nucleotides involved in each loop, and adopt different quadruplex conformations, potentially allowing differential recognition by small molecules that do not target the tetrads per se . As a control we used a sequence that forms a duplex DNA in solution.…”
Section: Resultsmentioning
confidence: 99%